An application of a modified constructive heuristic algorithm to transmission expansion planning - Zeinaddini-Maymand, M.; Rashidinejad, M.; Mohammadian, M.; Mahmoudabadi, A.; Khorasani, H. [UNESP]; Rahmani, M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Transmission expansion planning (TEP) is a non-convex optimization problem that can be solved via different heuristic algorithms. A variety of classical as well as heuristic algorithms in literature are addressed to solve TEP problem. In this paper a modified constructive heuristic algorithm (CHA) is proposed for solving such a crucial problem. Most of research papers handle TEP problem by linearization of the non-linear mathematical model while in this research TEP problem is solved via CHA using non-linear model. The proposed methodology is based upon Garver's algorithm capable of applying to a DC model. Simulation studies and tests results on the well known transmission network such as: Garver and IEEE 24-bus systems are carried out to show the significant performance as well as the effectiveness of the proposed algorithm. © 2011 IEEE.
Keywords: Constructive heuristic algorithm; DC model; Load-Shedding; Non-linear problem; Transmission expansion planning; Load-shedding; Nonlinear problems; Computer simulation; Convex optimization; DC power transmission; Expansion; Mathematical models; Problem solving; Sustainable development; Thermoelectric power; Heuristic algorithms